A comparison of risk stratification schemes for stroke in 79 884 atrial fibrillation patients in general practice - VAN STAA, T. P.; SETAKIS, E.; DI TANNA, G. L.; LANE, D. A.; LIP, G. Y. H. (Journal of thrombosis and haemostasis, 2011)
Background:  Anticoagulation management of patients with atrial fibrillation (AF) should be tailored individually on the basis of ischemic stroke risk. The objective of this study was to compare the predictive ability of 15 published stratification schemes for stroke risk in actual clinical practice in the UK. Methods:  AF patients aged ≥ 18 years in the General Practice Research Database, which contains computerized medical records, were included. The c‐statistic was estimated to determine the predictive ability for stroke for each scheme. Outcomes included stroke, hospitalizations for stroke, and death resulting from stroke (as recorded on death certificates). Results:  The study cohort included 79 844 AF patients followed for an average of 4 years (average of 2.4 years up to the start of warfarin therapy). All risk schemes had modest discriminatory ability in AF patients, with c‐statistics for predicting events ranging from 0.55 to 0.69 for strokes recorded by the general practitioner or in hospital, from 0.56 to 0.69 for stroke hospitalizations, and from 0.56 to 0.78 for death resulting from stroke as reported on death certificates. The proportion of patients assigned to individual risk categories varied widely across the schemes, with the proportion categorized as moderate risk ranging from 12.7% (CHA2DS2‐VASc) to 61.5% (modified CHADS2). Low‐risk subjects were truly low risk (with annual stroke events < 0.5%) with the modified CHADS2, National Institute for Health and Clinical Excellence and CHA2DS2‐VASc schemes. Conclusion:  Current published risk schemes have modest predictive value for stroke. A new scheme (CHA2DS2‐VASc) may discriminate those at truly low risk and minimize classification of subjects as intermediate/moderate risk. This approach would simplify our approach to stroke risk stratification and improve decision‐making for thromboprophylaxis in patients with AF.